Fuzzy Internal Direct Product - Tawfiq, L.N.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The purpose of this research is to show a constructive method for using known fuzzy groups as building blocks to form more fuzzy subgroups. As we shall describe employing this procedure with the fuzzy generating subgroups give us a large class of fuzzy subgroup of abelian groups which include all fuzzy subgroup of abelian groups of finite order.